EFFECT OF FUNGICIDES AND PLANT EXTRACTS ON UREDOSPORES GERMINATION OF PUCCINIA RECONDITA F. SP. TRITICI - R. F. CHAUDHARY,; M. G. CHAUDHARI, (The Bioscan, 2012)
Wheat is the most important food crop in the world. Of the three rusts, leaf rust caused by Puccinia recondita Rob. Ex. Desm. f. sp. tritici is the most important fungal disease of wheat which inflicting heavy losses in different parts of the country. In vitro evaluation of non-systemic fungicides revealed that maximum inhibition of uredospores germination was observed in mancozeb (54.85%) followed by chlorothalonil (40.89%). Among the different concentrations tried, the maximum inhibition of uredospores germination was at 1000 ppm of mancozeb which inhibited 83.33 per cent uredospores germination followed by same fungicide with 500 ppm (72.31%). Among systemic fungicides, propiconazole found the best for inhibition of 86.03 per cent uredospores germination followed by hexaconazole and penconazole with 77.40 and 72.29 per cent, respectively. Out ot 20 plant extracts, maximum per cent germination of rust uredospores inhibition was recorded in garlic (Allium sativum) bulb extract followed by onion (Allium cepa) bulb and ginger (Zingiber officinal) rhizome with 59.78, 57.70 and 54.81 per cent, respectively.